Programma: 14 november Mike Scott; 15 november Little Feat; 19 november ABC; 16 november Guru's Jazzmatazz
Programma: 14 november Mike Scott; 15 november Little Feat; 19 november ABC; 16 november Guru's Jazzmatazz.